(untitled) (Cambridge, 2002)
This collection of original contributions by an international group of experts summarizes recent developments in Genizah research. It begins with an overview of a century of work on the famous Taylor-Schechter Collection of Hebrew manuscripts at Cambridge University Library. The essays are an introduction to important intellectual, religious and social developments in the Jewish communities of the medieval Islamic world. They appeal to scholars with interests in Hebrew and Jewish studies, semitics, religious studies and aspects of medieval history
Keywords: Jews,Judaism,Cairo Genizah,Lịch sử người Do thái; History,Sacred books,Congresses; 70-1789